This preview shows page 1. Sign up to view the full content.
Unformatted text preview: lim x f ( x ) = lim x f ( x ) = lim x 5 x e 2 x = 0 because e 2 x approaches infinity faster than 5 x 3. (4 pts) Let g ( x ) = x 2 + ln( x ) + e 3.4 x + p x 3 + e 2 x a) Find g ( x ) : g ( x ) = e 3.4 x x 3 b) Find g ( x ) : g ( x ) = ln( x ) or p c) Evaluate lim x g ( x ) without using LHpitals Rule (show work!) lim x f ( x ) = lim x f ( x ) = lim x e 3.4 x x 3 = because e 3.4 x approaches infinity faster than x 3...
View Full
Document
 Spring '08
 Johnson
 Math, Calculus, Logic

Click to edit the document details